Answer:
Given the equation: ![3x^2+10x+c =0](https://tex.z-dn.net/?f=3x%5E2%2B10x%2Bc%20%3D0)
A quadratic equation is in the form:
where a, b ,c are the coefficient and a≠0 then the solution is given by :
......[1]
On comparing with given equation we get;
a =3 , b = 10
then, substitute these in equation [1] to solve for c;
![x_{1,2} = \frac{-10\pm \sqrt{10^2-4\cdot 3 \cdot c}}{2 \cdot 3}](https://tex.z-dn.net/?f=x_%7B1%2C2%7D%20%3D%20%5Cfrac%7B-10%5Cpm%20%5Csqrt%7B10%5E2-4%5Ccdot%203%20%5Ccdot%20c%7D%7D%7B2%20%5Ccdot%203%7D)
Simplify:
![x_{1,2} = \frac{-10\pm \sqrt{100- 12c}}{6}](https://tex.z-dn.net/?f=x_%7B1%2C2%7D%20%3D%20%5Cfrac%7B-10%5Cpm%20%5Csqrt%7B100-%2012c%7D%7D%7B6%7D)
Also, it is given that the difference of two roots of the given equation is
i.e,
![x_1 -x_2 = \frac{14}{3}](https://tex.z-dn.net/?f=x_1%20-x_2%20%3D%20%5Cfrac%7B14%7D%7B3%7D)
Here,
, ......[2]
.....[3]
then;
![\frac{-10 + \sqrt{100- 12c}}{6} - (\frac{-10 + \sqrt{100- 12c}}{6}) = \frac{14}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-10%20%2B%20%5Csqrt%7B100-%2012c%7D%7D%7B6%7D%20-%20%28%5Cfrac%7B-10%20%2B%20%5Csqrt%7B100-%2012c%7D%7D%7B6%7D%29%20%3D%20%5Cfrac%7B14%7D%7B3%7D)
simplify:
![\frac{2 \sqrt{100- 12c} }{6} = \frac{14}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%20%5Csqrt%7B100-%2012c%7D%20%7D%7B6%7D%20%3D%20%5Cfrac%7B14%7D%7B3%7D)
or
![\sqrt{100- 12c} = 14](https://tex.z-dn.net/?f=%5Csqrt%7B100-%2012c%7D%20%3D%2014)
Squaring both sides we get;
![100-12c = 196](https://tex.z-dn.net/?f=100-12c%20%3D%20196)
Subtract 100 from both sides, we get
![100-12c -100= 196-100](https://tex.z-dn.net/?f=100-12c%20-100%3D%20196-100)
Simplify:
-12c = -96
Divide both sides by -12 we get;
c = 8
Substitute the value of c in equation [2] and [3]; to solve ![x_1 , x_2](https://tex.z-dn.net/?f=x_1%20%2C%20x_2)
![x_1 = \frac{-10 + \sqrt{100- 12\cdot 8}}{6}](https://tex.z-dn.net/?f=x_1%20%3D%20%5Cfrac%7B-10%20%2B%20%5Csqrt%7B100-%2012%5Ccdot%208%7D%7D%7B6%7D)
or
or
![x_1 = \frac{-10 + \sqrt{4}}{6}](https://tex.z-dn.net/?f=x_1%20%3D%20%5Cfrac%7B-10%20%2B%20%5Csqrt%7B4%7D%7D%7B6%7D)
Simplify:
![x_1 = \frac{-4}{3}](https://tex.z-dn.net/?f=x_1%20%3D%20%5Cfrac%7B-4%7D%7B3%7D)
Now, to solve for
;
![x_2 = \frac{-10 - \sqrt{100- 12\cdot 8}}{6}](https://tex.z-dn.net/?f=x_2%20%3D%20%5Cfrac%7B-10%20-%20%5Csqrt%7B100-%2012%5Ccdot%208%7D%7D%7B6%7D)
or
or
![x_2 = \frac{-10 - \sqrt{4}}{6}](https://tex.z-dn.net/?f=x_2%20%3D%20%5Cfrac%7B-10%20-%20%5Csqrt%7B4%7D%7D%7B6%7D)
Simplify:
![x_2 = -2](https://tex.z-dn.net/?f=x_2%20%3D%20-2)
therefore, the solution for the given equation is:
and -2.
First find the slope of the line connecting these two points:
6-5
m = ------------ = -1/2
-4+2
Substitute this slope into y = mx + b: y = (-1/2)x + b.
Next, subst. 5 for y and -2 for x, and find b:
5 = (-1/2)(-2) + b, or 5-1=b. Then b = 4, and
the equation of the line is y = (-1/2)x + 4.
Answer:
I just finished this in math :) I'm pretty sure it's -3<x<2
Answer:
![x^3-8x^2+5x+14](https://tex.z-dn.net/?f=x%5E3-8x%5E2%2B5x%2B14)
Step-by-step explanation:
We have been given the zeroes of polynomial which are -1,2,7
That means the factors are (x+1) (x-2) (x-7)
When we want to a polynomial from zeroes we multiply the factors
![(x+1)(x-2)(x-7)](https://tex.z-dn.net/?f=%28x%2B1%29%28x-2%29%28x-7%29)
![(x+1)(x^2-7x-2x+14)](https://tex.z-dn.net/?f=%28x%2B1%29%28x%5E2-7x-2x%2B14%29)
![(x+1)(x^2-9x+14)](https://tex.z-dn.net/?f=%28x%2B1%29%28x%5E2-9x%2B14%29)
![(x^3-9x^2+14x+x^2-9x+14](https://tex.z-dn.net/?f=%28x%5E3-9x%5E2%2B14x%2Bx%5E2-9x%2B14)
![x^3-8x^2+5x+14](https://tex.z-dn.net/?f=x%5E3-8x%5E2%2B5x%2B14)
Hence, the required polynomial is:
![x^3-8x^2+5x+14](https://tex.z-dn.net/?f=x%5E3-8x%5E2%2B5x%2B14)